Civil cassation: Genesis and receipt of motion for cassation in the Peruvian civil law - Távara Córdova, Francisco (2019)
The article analyzes the evolution of the civil cassation, from a historic perspective, from its initial receipt and adequation in our legal system to its current configuration, as well as its problematic and possibilities of systemic and integral reform that rationalizes the activity of the cassation organs of the Supreme Court of Justice of the Republic, reduce the case load and ensure the equality of the parties in the process, in order to ensure full compliance with the purposes of cassation and ensure the principle of predictability of court decisions in the field of civil justice.